Ultrafine Ni₀.₈₅Se nanoparticles encapsulated inside hollow porous carbon spheres and their excellent Na storage performance - Xi, J. C. (2024)
As a novel anode material for sodium-ion batteries, ultrafine Ni0.85Se nanoparticles encapsulated inside hollow porous carbon spheres (HPCS@Ni0.85Se) are prepared by impregnating Ni(NO3)2 into HPCSs, calcination and selenization, which is based on the strong capillary effect of HPCSs. Material characterization reveals that Ni0.85Se nanoparticles with a diameter of 5–15 nm are evenly dispersed and intimately coupled to the internal wall of HPCSs, and the content of Ni0.85Se reaches 52.81%. HPCSs as unique reactors and Ni0.85Se carriers improve electronic conductivity of Ni0.85Se, facilitate electrolyte penetration and storage, buffer volume variation of Ni0.85Se, effectively confine Ni0.85Se during long-term cycles. Consequently, HPCS@Ni0.85Se exhibits excellent cycling durability and extraordinary rate capability. High reversible capacities of 341 mA h g−1 at 1 A g−1 after 1000 cycles, 280 mA h g−1 at 5 A g−1 after 2000 cycles and 305 mA h g−1 at 10 A g−1 after 540 cycles are achieved. The reaction kinetics and Na + storage mechanism are further analyzed by galvanostatic intermittent titration technique, cyclic voltammetry and electrochemical impedance spectra measurements. Ex-situ characterizations confirm outstanding structural stability of HPCS@Ni0.85Se. It is demonstrated that HPCS@Ni0.85Se is an excellent anode material, and this unique HPCS-based nanoencapsulation structure is an effective composite strategy for transition metal selenides.